2017
DOI: 10.1021/jacs.7b07606
|View full text |Cite
|
Sign up to set email alerts
|

Operando Spectroscopic Analysis of CoP Films Electrocatalyzing the Hydrogen-Evolution Reaction

Abstract: Transition metal phosphides exhibit high catalytic activity toward the electrochemical hydrogenevolution reaction (HER) and resist chemical corrosion in acidic solutions. For example, an electrodeposited CoP catalyst exhibited an overpotential, η, of −η < 100 mV at a current density of −10 mA cm −2 in 0.500 M H 2 SO 4 (aq). To obtain a chemical description of the material asprepared and also while effecting the HER in acidic media, such electrocatalyst films were investigated using Raman spectroscopy and X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(89 citation statements)
references
References 37 publications
13
76
0
Order By: Relevance
“…Figure S2c). The Raman peaks, which we attributed to CoP x , match with the Raman spectrum of electrodeposited CoP/CoP x O y mixed electrodes reported by Saadi et al . There, the question of the exact composition of the Raman‐active phase remained unanswered.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Figure S2c). The Raman peaks, which we attributed to CoP x , match with the Raman spectrum of electrodeposited CoP/CoP x O y mixed electrodes reported by Saadi et al . There, the question of the exact composition of the Raman‐active phase remained unanswered.…”
Section: Resultssupporting
confidence: 84%
“…Moreover, it was also found that an increasing P/metal ratio of TMP yields an increase in HER performance which is also reflected in decreasing Tafel slopes ,,. Thus, transition metal phosphides, including nickel phosphides, cobalt phosphides, iron phosphides, molybdenum phosphides,,, tungsten phosphides,, copper phosphides and their alloys have emerged as potential HER electrocatalysts. In order to increase the apparent electrochemical activity, porous conductive substrates such as carbon cloths and nickel foams are often used as current collectors.…”
Section: Introductionmentioning
confidence: 99%
“…Communications previously. [20] Thel ower white-line amplitude for Ni 0.1 Co 0.9 Ps uggests an increase in the Co oxidation state after the Ni addition, which is in agreement with the first derivative analysis (Figure S34), [21] XPS results (Figure 3a)a nd l-edge measurements ( Figure S35 to S37). From XANES,t he higher intensity of Co Kp re-edge peak of Ni 0.1 Co 0.9 Pd emonstrates the electron transfer caused by Ni addition, analogous to aprior report on Co 0.1 Fe 0.9 Scatalyst.…”
Section: Angewandte Chemiesupporting
confidence: 83%
“…The metal phosphides can be facilely deposited onto the conductive substrate surfaces by the reduction reaction of metal ions and H 2 PO 2 − . In general, this method is only applicable to the synthesis of specific metal phosphides, such as CoP, NiP, and the yielded metal phosphides mainly present amorphous features and complex composition …”
Section: Synthesis Of Nanostructured Transition Metal Phosphidesmentioning
confidence: 99%